Driver's Face Tracking Based On Improved CAMShift for Drowsiness Detection - Jie, Ma; Rui, Xiao; Kamarul Hawari, Ghazali (Natural Sciences Publishing Cor., 2013)
The statistic shows that the number of casualty increase in every year due to road accident related to driver drowsiness. After long journey or sleepless night, vehicle driver will perform some bio-features with regard to drowsiness on them face. It is self-evident that getting location information of face in continuous monitoring and surveillance system rapidly and accurately can help prevent many accidents, and consequently save money and reduce personal suffering. In this paper, according the real situation in vehicle, an improved CAMShift approach is proposed to tracking motion of driver’s head. Results from experiment show the significant performance of proposed approach in driver’s head tracking.